(untitled) - Vaculik, Juraj; Benech, Peter (Doprava a spoje, 2007)
Contribution is about some payment systems in internet environment such as Online payment including system of micro payment. There is some short introduction to payment systems with focus to direct payment. Paper shows communication of system in particular payment systems. Partly pointed out to shortness of systems such as their security eventually payment of services.